Physicochemical Characterization of Broken Rice and Analysis of Its Volatile Compounds - LOYDA, Charupa; SINGANUSONG, Riantong; JARANRATTANASRI, Arporn; TOCHAMPA, Worasit (Walailak Journal of Science and Technology (WJST), 2021)
The term “broken rice” refers to fragments of rice grains broken during the milling process. Broken rice is generally classified into 3 sizes: large, medium, and small. Broken rice can be widely used for the pet food industry, livestock feeding, aquaculture, laundry starch, cosmetics, and textile manufacture. The purpose of this study was to determine certain properties of raw large broken rice (LBR) and small broken rice (SBR) of 4 commercially important varieties: Khao Dawk Mali105 (KDML105), Pathumtani1 (PTT1), Chainat1 (CN1), and Kor-khor6 (RD6). The properties analyzed were pasting properties, alkali spreading value, gel consistency, chemical composition, and amylose content. Volatile components of the LBR and SBR samples were also identified. Results revealed that each rice variety had different rheological characteristics. SBR of KDML105, PTT1, and CN1 had alkaline spreading value (ASV) in the range of 3 - 7. The rice flour gel of the glutinous rice variety RD6 showed the highest flow distance in both LBR and SBR forms. CN1 had the highest amylose content in both LBR and SBR forms, while RD6 had the lowest. Among all the samples, the 6 most abundant volatile components detected were alcohols, aldehydes, furans, ketones, sulfur, and terpenes. The 3 volatile compounds with the highest odor active values (OAV) in both LBR and SBR forms were hexanal, heptanal, and 3-methylbutanal.